Doppler-Shifted Alkali D Absorption as Indirect Evidence for Exomoons - Schmidt, Carl A. (Frontiers in Astronomy and Space Sciences, 2022)
Sodium and potassium signatures in transiting exoplanets can be challenging to isolate from the stellar absorption lines. Here, these challenges are discussed in the framework of Solar System observations, and transits of Mercury in particular. Radiation pressure is important for alkali gas dynamics in close-orbiting exoplanets since the D lines are efficient at resonant scattering. When the star-planet velocity is ≳10km/s, eccentric exoplanets experience more than an order of magnitude higher radiation pressures, aiding atmospheric escape and producing a larger effective cross-section for absorbing starlight at the phase of transit. The Doppler shift also aids in the isolating the planetary signature from the stellar photosphere’s absorption. Only one transiting exoplanet, HD 80606b, is presently thought to have both this requisite Doppler shift and alkali absorption. Radiation pressure on a planetary exosphere naturally produces blue-shifted absorption, but at levels insufficient to account for the extreme Doppler shifts that have been inferred from potassium transit measurements of this system. In the absence of clear mechanisms to generate such a strong wind, it is described how this characteristic could arise from an exomoon-magnetosphere interaction, analogous to Io-Jupiter. At low contrasts presented here, follow-up transit spectra of HD 80606b cannot rule out a potassium jet or some atmospheric species with broad absorption structure. However, it is evident that line absorption within the imaging passbands fails to explain the reported color differences. New observations of energetic alkalis produced by the Io-Jupiter interaction are also presented, which illustrate that energetic sodium Doppler structure offers a more valuable marker for the presence of an exomoon than potassium.